PERHATIAN ORANG TUA DAN KEDISIPLINAN TERHADAP PRESTASI BELAJAR SEJARAH - Popy Sopiyati (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2019)
The research aims to determine the effect of Parental Attention and Discipline on Historical Learning Achievement. The research method used in this study is a survey method with correlation and regression analysis. Variables Parental attention and data discipline were obtained through questionnaires, and data on historical learning achievement was obtained through multiple choice test questions on respondents. The results of the study concluded that: 1) There is a significant influence of parental attention and discipline together on the historical learning achievement of Private Vocational School students in South Jakarta. This is evidenced by the acquisition of Sig = 0,000 <0.05 and Fcount = 10.838. 2) There is a significant influence of parents' attention on the learning achievement of the history of private vocational students in South Jakarta. This is evidenced by the acquisition of Sig = 0,039 <0.05 and tcount = 0.115. 3) There is a significant influence of discipline on historical learning achievement of Private Vocational School students in South Jakarta. This is evidenced by the acquisition of Sig = 0,001 <0.05 and tcount = 3.687.